Ductal Carcinoma In Situ (DCIS) Diagnosed by MRI-Guided Biopsy among BRCA1/BRCA2 Mutation Carriers - Renata Faermann; Eitan Friedman; Orit Kaidar-Person; Jonathan Weidenfeld; Malka Brodsky; Anat Shalmon; Osnat Halshtok Neiman; Michael Gotlieb; Yael Yagil; David Samoocha; Dana Madorsky Feldman; Miri Sklair-Levy (Hindawi-Wiley, 2022)
Background. While BRCA1/BRCA2 pathogenic sequence variants (PSVs) clearly confer an increased risk for invasive breast cancer, the extent to which these mutant alleles increase DCIS risk is less clear. Objective. To assess the rate of detection over a 5-year period, and MRI imaging features of pure noncalcified DCIS in a cohort of Israeli BRCA1/BRCA2 PSV carriers attending a high-risk clinic from 2015 to 2020. Materials and Methods. All female BRCA1/BRCA2 PSV-carriers followed at the Meirav High-risk clinic from 2015 to 2020 were eligible if they underwent semiannual breast imaging (MRI/mammography) and MRI-guided biopsy-proven pure DCIS. Clinical data, pathology information, and imaging characteristics were retrieved from the computerized archiving system. Results. 18/121 (15.2%) participating BRCA1 PSV carriers and 8/81 (10.1%) BRCA2 PSV-carriers who underwent MRI-guided biopsy were diagnosed with DCIS. The median age of BRCA1 carriers and BRCA2 carriers was 49.8 years and 60.6 years, respectively (p=0.55). Negative estrogen-receptor tumors were diagnosed in 13/18 (72%) BRCA1 and 2/8 (25%) BRCA2 PSV carriers (p<0.05). Thirteen (13/18-72%) BRCA1 carriers had intermediate to high-grade or high-grade DCIS compared with 4/8 (50%) of BRCA2 carriers (p=0.03). Over the 5-year study period, 29/1100 (2.6%) BRCA1/BRCA2 PSV carriers were diagnosed with DCIS seen on MRI only. Conclusion. MRI-detected noncalcified DCIS is more frequent in BRCA1 PSV carriers compared with BRCA2 carriers, unlike the BRCA2 predominance in mammography-detected calcified DCIS. BRCA1-related DCIS is diagnosed earlier, more likely to be estrogen receptor-negative and of higher grade compared with BRCA2-related DCIS. Future prospective studies should validate these results and assess the actual impact they might have on clinical management of BRCA PSV carriers.